Condusivity Academic Climate to Improve the Quality of Entrepreneurship Education in Emerging Economies - Bagis, Abdul Azis; Nururly, Santi; Sukma, Akram; Mohamed, Zulkifflee (Jurnal Pendidikan Progresif, 2024)
Condusivity Academic Climate to Improve the Quality of Entrepreneurship Education in Emerging Economies. Objectives: This research aims to present a detailed empirical investigation to build the entrepreneurial orientation of business management students, which needs to rely on the strength of entrepreneurial intentions through a conducive academic environment. Methods: The methodology used in this research is associative research with the study of certain dependent, independent and mediating variables involving business management students from various state universities in West Nusa Tenggara. Sampling used a saturated sample of 97 business management students. According to the research model, the author chose a structural equation model (SEM) to analyze the data and support using the theory of planned behaviour (TPB) dimensions of entrepreneurial intentions with certain attitudes, perceived behavioural control, and subjective norms. Findings: The research results show that the three variables that form entrepreneurial intentions have been effective in building entrepreneurial orientation among students and becoming more meaningful through a conducive academic climate. Conclusion: This research provides detailed and solid results regarding entrepreneurial orientation that is more measurable and easier to realize by relying on the strength of entrepreneurial intentions in a conducive academic environment. Improving the quality of entrepreneurship education for business management students can utilize the results of this research as a guide. However, to maximize the entrepreneurial orientation of business management, students need to be mediated by an academic climate conducive to strengthening students' entrepreneurial intentions.Keywords:  entrepreneurship education, workplace spirituality, entrepreneurial orientation,  students’ entrepreneurial intention.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202466